1959
DOI: 10.1126/science.130.3385.1340
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitor in Immature Soybean Seeds and 2,4-D-Sprayed Soybean Seedlings

Abstract: A naturally occurring inhibitor of seed germination has been isolated by ion-exchange chromatography from soybean seeds and seedlings. The inhibitor was present in large amounts in immature seeds and in seedlings sprayed with 2,4-D. The inhibitor acted as an "uncoupler" when applied to soybean root tips or mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1960
1960
1972
1972

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Maximum absorbance of reagent ascorbic acid is at 265 nm and that of the purified elution sample is 260 nm. The material in peak 5 appears to be implicated in the regulation of radicle growth in the developing soybean seed and in 2,4-dichlorophenoxyacetic acid-treated soybean seedlings (Key and Galitz 1959).…”
Section: Resultsmentioning
confidence: 98%
“…Maximum absorbance of reagent ascorbic acid is at 265 nm and that of the purified elution sample is 260 nm. The material in peak 5 appears to be implicated in the regulation of radicle growth in the developing soybean seed and in 2,4-dichlorophenoxyacetic acid-treated soybean seedlings (Key and Galitz 1959).…”
Section: Resultsmentioning
confidence: 98%
“…In earlier experiments indications were obtained that 2,4-D induces the formation of a secretable growth inhibitor in the roots of pea seedlings (Eliasson 1959). Key and Galitz (1959) showed that 2,4-D increases the content of an inhibitor in soybean.…”
Section: Resultsmentioning
confidence: 98%
“…(75) extracted several grov;th-inhibiting and growthpromoting substances from the roots of maize. Soybean seedlings, particularly seedlings treated with 2,4-D, contain a compound which acts as an inhibitor of oxidative phosphorylation (90).…”
Section: Housley Etmentioning
confidence: 99%